Critical-point models to relate white oat yield and disease intensity of the multiple pathosystem leaf rust - Helminthosporium blight Modelos de pontos críticos para relacionar o rendimento de grãos de aveia branca com a intensidade de doença no patossistema múltiplo ferrugem da folha - Helmintosporiose - Nerbass Jr. J.M.* (2010)
The leaf rust and helminthosporium blight are the main foliar diseases of white oat. The chemical control in susceptible cultivars does not consider the economic damage threshold (EDT). The objective of this research was to obtain the damage functions by critical-point models to relate damage by simultaneous occurrence of white oat leaf rust and helminthosporium blight with yield grains during 2006/07 crop seasons in Lages, SC, Brazil. The gradient of diseases intensity was generated by number of applications and rates fungicides on cultivars 'UPFA 20' and 'UPFA 22'. The trials consisted by 10 treatments distributed in randomly blocks with four replications. Diseases evaluations were done in the elongation, booting and flowering stages. The critical-point models were obtained by linear regression between grain yield and leaf diseases incidence and severity. In 2006, significant function was obtained for 'UPFA 20' in booting stage (R=6.345- 22.07I), with 'UPFA 22'. The significant functions were obtained in elongation (R=5.726-17.96I and R=5.160-541.5S), booting (R=5.961-21.85I; R=5.433-966.8S) and flowering stages (R=6.217-36.41I; R=5.539-1.185S). In 2007, the significant functions were obtained in all growth stages evaluated. To 'UPFA 20', the significant functions were in the elongation (R=6.369-55.61I; R=4.965-2.911S), booting (R=6.620-49.91I; R=5.181-1.702S) and flowering (R=6.129-32.34I; R=5.252-638.6S), while in the 'UPFA 22', were in the elongation (R=5.201-41.96I; R=4.977-657.8S), booting (R=5.329-60.51I; R=4.238-798.1S) and flowering (R=5.604- 32.83I; R=4.680-588.5S). The 'UPFA 22' cultivar production was more affected by diseases occurrence and the diseases intensity in the flowering stage showed greater relation with the yield grain. The generated functions allowed obtaining the damage coefficient to use in the EDT in the multiple pathosystem leaf rust and helminthosporium.